A Rapid One-Step Immunoradiometric Assay for Factor VIII-Procoagulant Antigen Utilizing Monoclonal Antibodies - Stel, H V; Veerman, E C I; Huisman, J G; Janssen, M C; van Mourik, J A (Thrombosis and Haemostasis, 1983)
A two-site immunoradiometric assay for factor VIII-procoagulant antigen (VIIICAg) that relies completely on monoclonal antibodies has been developed. By selecting an appropriate combination of these antibodies, it was possible to develop an assay in which the radiolabelled monoclonal antibody did not inhibit the binding of antigen to the solid-phase monoclonal antibodies. Thus, the entire test could be carried out as a one-step procedure. With this one-step assay, an amount of 0.0025 U VIIICAg/ml plasma could be detected after 4 hr of incubation, whereas 18 hr of incubation resulted in a lower limit of sensitivity of 0.0005 U VIIICAg/ml. The use of a one-step assay provides a significant advantage over the conventional two-step assay by simplifying, shortening and rendering the performance of the assay more convenient.
Keywords: Monoclonal antibodies; One-step IRMA; VIIICAg; Haemophilia A